Pengaruh Karakteristik Pekerjaan terhadap Work Life Balance - Jihan Denisa; Sri Suwarsi (Bandung Conference Series: Business and Management, 2024)
Abstract. Human resources are one of the capital that must be owned so that an organization's goals are achieved. Developing human resources aims to have skills, competence and ability to build a better work environment. This research aims to determine the influence of work on work life balance.This research is to examine and analyze the job characteristics of the Center for Competency Development of Natural Resources and Settlements BPSDM Ministry of PUPR, to find out and analyze how the Work-Life Balance Case Study of Employees of the Center for Competency Development of Natural Resources and Settlements BPSDM Ministry of PUPR is, to find out and analyze how big awards influence Work on Work-Life Balance Case Study of Employees of the Center for Competency Development of Natural Resources and Settlements BPSDM Ministry of PUPR.This research was conducted at the BPSDM Ministry of PUPR's Natural Resources and Settlement Competency Development Center. The population in this study was 77 employees and the sample for this study was all employees. The type of research used is quantitative, using the census method.Based on this research, it shows that the influence of Job Characteristics on Work Life Balance carried out by employees at the Center for Competency Development of Natural Resources and Settlements, BPSDM, Ministry of PUPR, shows that the calculated t value obtained is 4,039 > t table of 1,992. The criteria for testing the hypothesis are that Ho is rejected and Ha received a significant and positive influence with an influence contribution of 52.2%. Abstrak. Sumber daya manusia sebagai salah satu modal yang harus dimiliki agar tujuan sebuah organisasi tercapai. Mengembangkan sumber daya manusia bertujuan agar memiliki keterampilan, kompeten dan mampu dalam bangun lingkungan kerja yang lebih baik. Penelitian ini bertujuan untuk mengetahui pengaruh karakteristik Pekerjaan Terhadap Work Life Balance. Penelitian ini untuk mengkaji dan menganalisis bagaimana karakteristik pekerjaan Pusat Pengembangan Kompetensi SDA dan Permukiman BPSDM Kementerian PUPR, untuk mengetahui dan menganalisis bagaimana Kasus Studi Work-Life Balance Pada Karyawan Pusat Pengembangan Kompetensi SDA dan Permukiman BPSDM Kementerian PUPR, untuk mengetahui dan menganalisis bagaimana penghargaan besar Pengaruh Pekerjaan Terhadap Work Life Balance Studi Kasus Pada Karyawan Pusat Pengembangan Kompetensi SDA dan Permukiman BPSDM Kementerian PUPR. Penelitian ini dilakukan di Pusat Pengembangan Kompetensi SDA Dan Permukiman BPSDM Kementerian PUPR. Populasi dalam penelitian ini berjumlah 77 pegawai dan sampel dari penelitian ini adalah seluruh karyawan. Jenis penelitian yang digunkan adalah kuantitatif, dengan menggunakan metode sensus. Berdasarkan dari penelitian ini menunjukan bahwa pengaruh Karakteristik Pekerjaan terhadap Work Life Balance yang dilaksanakan oleh karyawan di pusat Pusat Pengembangan Kompetensi SDA dan Permukiman BPSDM Kementerian PUPR, menunjukan nilai t hitung yang diperoleh sebesar 4.039 > t tabel sebesar 1.992 kriteria pengujian hipotesis bahwa Ho ditolak dan Ha diterima berpengaruh signifikan dan positif dengan kontribusi pengaruh sebesar 52.2%.